In Silico Analysis, Synthesis, and Biological Evaluation of Triazole Derivatives as H1 Receptor Antagonist - Badeliya, Sandip N.; Panchal, Ishan I.; Panigrahi, Bibhuranjan; Patel, C. N. (Current Drug Discovery Technologies, 2021)
Introduction: Histamine, a biological amine, is considered as a principal mediator of many pathological processes regulating several essential events in allergies and autoimmune diseases. Numerous derivatives have been developed that strive with histamine at the H1 receptor and prevent binding of histamine at the H1 receptor, thereby preventing allergic reactions. Molecules containing a triazole ring fused with six-membered ring systems are found to possess broad applications in the field of medicine and industry. The present study is an attempt to characterize the impact of the nature of the substituent introduced at 5 positions of the-4H-1,2,4-triazole-3-thiol on their capacities to bind with the H1 receptor. Methods: Molecular docking (PDB ID: 3RZE) revealed that synthesized derivatives and target proteins were actively involved in binding with Tyr-108, Thr-112, Ala-216, and Phe-432 subunits. A pharmacophore model, new 5-(4-substituted phenyl)-4-(phenylamino)-4-H-1,2,4-triazole-3- thiols (5a-5h) were designed and evaluated for H1-blocking activity using isolated segments from the guinea pig ileum. Results: According to in silico analysis, all the compounds have a topological polar surface area (TPSA) less than 140 Å squared, so they tend to easily penetrate cell membranes. The results show that most of the compounds are non-inhibitors of CYP450 substrates that play a fundamental role in drug metabolism. Compounds 5d (50.53±12.03), 5h (50.62±12.33) and 7a (55.07±12.41) are more active than others. Conclusion: Finally, these derivatives were screened for H1 receptor antagonist activity using guinea pig ileum, taking chlorpheniramine maleate as a standard. Most of the compounds were found to possess better antihistamine activity.
Keywords: guinea pig ileum